Cysteamine Eye Drops in Hyaluronic Acid Packaged in Innovative Single-Dose Systems, Part II: Long-Term Stability and Clinical Ocular Biopermanence - Ana Castro-Balado; Andrea Cuartero-Martínez; Hugo Pena-Verdeal; Gonzalo Hermelo-Vidal; Anja Schmidt; Belén Montero; Manuela Hernández-Blanco; Irene Zarra-Ferro; Miguel González-Barcia; Cristina Mondelo-García; María Jesús Giráldez; Eva Yebra-Pimentel; et al. (MDPI AG, 2023)
Background: Cystinosis is a rare genetic disorder characterized by the accumulation of cystine crystals in several tissues and organs causing, among others, severe eye symptoms. The high instability of cysteamine eye drops makes it difficult to develop formulations with an acceptable shelf life to be prepared in hospital pharmacy departments. Previously, a new compounded formulation of cysteamine eye drops in hyaluronic acid (HA) packaged in innovative single-dose systems was developed. Methods: Long-term stability at −20 °C of this formulation was studied considering the content of cysteamine, pH, osmolality, viscosity, and microbiological analysis. The oxygen permeability of single-dose containers was also studied and an ocular biopermanence study was conducted in healthy volunteers measuring lacrimal stability and volume parameters. Results: Data confirm that cysteamine concentration remained above 90% for 120 days, all parameters remaining within the accepted range for ophthalmic formulations. The permeability of the containers was reduced over time, while ocular biopermanence was maintained despite the freezing process and storage time. Conclusions: 0.55% cysteamine hydrochloride formulation in HA and packaged in single-dose containers preserved at −20 °C is stable for 120 days protected from light, presenting high potential for its translation into clinical practice when commercial presentations are not available.